Synthetic polyploid induction influences morphological, physiological, and photosynthetic characteristics in Melissa officinalis L. - Bharati, Rohit; Gupta, Aayushi; Novy, Pavel; Severová, Lucie; Šrédl, Karel; Žiarovská, Jana; Fernández-Cusimamani, Eloy (Frontiers in Plant Science, 2023)
Melissa officinalis L., a well-known herb with diverse industrial and ethnopharmacological properties. Although, there has been a significant lack in the breeding attempts of this invaluable herb. This study aimed to enhance the agronomical traits of M. officinalis through in vitro polyploidization. Nodal segments were micropropagated and subjected to oryzalin treatment at concentrations of 20, 40, and 60 mM for 24 and 48 hours. Flow cytometry, chromosome counting, and stomatal characteristics were employed to confirm the ploidy level of the surviving plants. The survival rate of the treated explants decreased exponentially with increasing oryzalin concentration and duration. The highest polyploid induction rate (8%) was achieved with 40 mM oryzalin treatment for 24 hours. The induced tetraploid plants exhibited vigorous growth, characterized by longer shoots, larger leaves, and a higher leaf count. Chlorophyll content and fluorescence parameters elucidated disparities in photosynthetic performance between diploid and tetraploid genotypes. Tetraploid plants demonstrated a 75% increase in average essential oil yield, attributed to the significantly larger size of peltate trichomes. Analysis of essential oil composition in diploid and tetraploid plants indicated the presence of three major components: geranial, neral, and citronellal. While citronellal remained consistent, geranial and neral increased by 11.06% and 9.49%, respectively, in the tetraploid population. This effective methodology, utilizing oryzalin as an anti-mitotic agent for polyploid induction in M. officinalis, resulted in a polyploid genotype with superior morpho-physiological traits. The polyploid lemon balm generated through this method has the potential to meet commercial demands and contribute significantly to the improvement of lemon balm cultivation.